Association between climatic conditions, population density and COVID-19 in Indonesia - R. Azizah,; Martini, Santi; Lilis Sulistyorini,; Mahmudah,; Pawitra, Aditya Sukma; Budijanto, Didik; Nagari, Stefanny Surya; Fitrahanjani, Cendana; Ramadhani, Fairuz Haniyah; Mohd. Talib Latif, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The first emergence of Corona Virus Disease 2019 (COVID-19) confirmed cases found in Wuhan, China, has become a global crisis. At least 177 countries have been affected over 43,000,000 confirmed cases of corona positive and more than one million deaths until October 27th, 2020. Recent research has analyzed any possible factors causing the COVID-19 spreads were climate factors and population density. Indonesia was a tropical region known as the high-populated country in the World, with a 52.9% area with a high mean air temperature and over 267.7 million populations. Our study aims to analyze the correlation between climate, population density, and COVID-19 in Indonesia. We used the K-means cluster method and Fisher’s exact test to determine climatic conditions, population density, and COVID-19 clusters and study the correlation. Our research found that there is a correlation between climatic conditions and population density with COVID-19 (p: 0,034; p:0,004). Warmer climate conditions and densely populated regions contributed to the risen COVID-19 transmission in Indonesia. These are highlighted by the evidence of the top six provinces with highest COVID-19 cases are province classified in warmer climatic conditions (high air temperature, low rainfall, and humidity) and a fairly-dense to densely populated region.